Ecological Education as a Basis for an Ecological Culture of the Russian Society - SHOTAEVNA KHETAGUROVA, Valeriya; IAKOVLEVA YURIEVNA, Irina; ANATOLYEVNA BRYUKHANOVA, Galina; ALEKSANDROVNA DENIKAEVA, Ekaterina; VIKTOROVNA TOLBUZINA, Tatyana (Journal of Environmental Management and Tourism, 2016)
The article deals with the forming of an ecological culture in Russian society issues. Ecological culture is considered as the dialectic of relationship of the environment and a person. Continuous universal ecological education is the necessary condition and the basis of the establishment of an ecological culture. In the article the essence and the objective necessity of the continuity of an ecological education are defined, historical-culture process of the development of this education in Russia is shown, the analysis of the social policy in the educational sphere is conducted, main directions of the creation of united system of continuous ecological education are shown.
Keywords: ecological culture; education; ecological enlightenment; ecological problems; ecologization of the society